The real effects of relationship lending✰ - Banerjee, Ryan N.; Gambacorta, Leonardo; Sette, Enrico (Journal of Financial Intermediation, 2021)
This paper studies the real effects of relationship lending on firm activity in Italy following Lehman Brothers’ default shock and Europe's sovereign debt crisis, two different crisis situations where in the latter, bank solvency was at the centre of the economic shock while being more peripheral in the former. We use a large data set that merges the comprehensive Italian Credit and Firm Registers. We find that following Lehman's default, banks offered more favourable continuation lending terms to firms with which they had stronger relationships. Such favourable conditions enabled firms to maintain higher levels of investment and employment. The insulation effects of tighter bank-firm relationships were still present during the European sovereign debt crisis, especially for firms tied to well capitalised banks.